A critical review on extraction, characteristics, physicochemical activities, potential health benefits, and industrial applications of fucoidan. Issue 4 (30th July 2022) - Du, Bin; Zhao, Qiancheng; Cheng, Caihong; Wang, Huiying; Liu, Yanfei; Zhu, Fengmei; Yang, Yuedong
Abstract: Fucoidan is a kind of sulfated polysaccharide that consists mainly of fucose and is found in marine brown alga. Fucoidan is a major bioactive compound in brown seaweeds known to have biological activities including anticancer, anti‐inflammatory, antioxidant, anticoagulant, antithrombotic, antivirus, hypolipidemic, and immune‐modulating properties. Due to the adhesive property of fucoidan, it can increase endothelial cell adhesion and proliferation. An increasing number of investigations in the past few years have demonstrated the extraction process of fucoidan. However, the critical review of fucoidan in health benefits has been less explored. In this review, the recent advances of fucoidan were summarized. Moreover, the extraction and purification processes, the characterization of structure, as well as its physicochemical activities, biological activities, and industrial applications were discussed. This review will provide fundamental information for future investigation on controlling the structure, purity, and consistency of the fucoidan product. Abstract : The extraction and purification processes and the characterization of the structure of fucoidan were reviewed. The physicochemical activities, biological activities, and industrial applications of fucoidan were discussed.